MLL‐rearranged acute lymphoblastic leukaemia stem cell interactions with bone marrow stroma promote survival and therapeutic resistance that can be overcome with CXCR4 antagonism. (7th January 2013) - Sison, Edward Allan R.; Rau, Rachel E.; McIntyre, Emily; Li, Li; Small, Donald; Brown, Patrick
Summary Infants with MLL‐rearranged (MLL‐R) acute lymphoblastic leukaemia (ALL) have a dismal prognosis. While most patients achieve remission, approximately half of patients recur with a short latency to relapse. This suggests that chemotherapy‐resistant leukaemia stem cells (LSCs) survive and can recapitulate the leukaemia. We hypothesized that interactions between LSCs and the bone marrow microenvironment mediate survival and chemotherapy resistance in MLL‐R ALL. Using primary samples of infant MLL‐R ALL, we studied the influence of bone marrow stroma on apoptosis, proliferation, and cytotoxicity induced by the FLT3 inhibitor lestaurtinib. MLL‐R ALL were differentially protected by stroma from spontaneous apoptosis compared to non‐MLL‐R ALL. Co‐culture of bulk MLL‐R ALL in direct contact with stroma or with stroma‐produced soluble factors promoted proliferation and cell cycle entry. Stroma also protected bulk MLL‐R ALL cells and MLL‐R ALL LSCs from lestaurtinib‐mediated cytotoxicity. Previous studies have demonstrated that CXCR4 mediates bone marrow microenvironment signalling. Using a xenograft model of MLL‐R ALL, we demonstrated that CXCR4 inhibition with AMD3100 (plerixafor) led to markedly enhanced efficacy of lestaurtinib. Therefore, the bone marrow microenvironment is a mediator of chemotherapy resistance in MLL‐R ALL and targeting leukaemia‐stroma interactions with CXCR4 inhibitors may prove useful in this high‐risk subtype of paediatric ALL.